The Relationship Between Intrauterine Device (IUD) Contraception and Sexual Pleasure in Reproductive-Age Couples at Kusuma Pertiwi Clinic - Yusti Anggi Umbu Pingge (IRDH International Journal of Technology, Agriculture and Natural Sciences, 2026)
Sexual pleasure related to Intrauterine Device (IUD) can be disturbed during intercourse. The purpose of this study is to determine the relationship between IUD contraception and sexual pleasure in couples of reproductive age (PUS) at Kusuma Pertiwi Clinic. The research design used in this study is an Analytical Correlational study with a cross-sectional approach. The sampling technique used is Simple Random Sampling. The population consisted of 42 people and the sample comprised 38 people. The independent variable is the IUD contraceptive, and the dependent variable is sexual satisfaction. The statistical test used is Spearman-Rho with a significance value of < 0.05. The research results regarding IUD contraception showed that almost all couples of reproductive age (PUS) felt comfortable after having the IUD inserted, totaling 31 people (81.6%) out of 38 people. Research on sexual satisfaction shows that most couples of reproductive age (CRA) after having an IUD inserted reported sexual satisfaction at a very satisfying level, with 26 people (68.4%) out of 38. Based on the analysis of the relationship using Spearman's Rho, the result obtained a p-value of 0.000 < α = 0.05, which means Ho is rejected, with a correlation coefficient of 0.817, indicating a very strong relationship. The conclusion is that there is a relationship between IUD contraception and sexual pleasure in couples of reproductive age, making IUD users very comfortable during sexual activity.